2010
DOI: 10.1039/b918970j
|View full text |Cite
|
Sign up to set email alerts
|

Hydroamination reactions by metal triflates: Brønsted acid vs. metal catalysis?

Abstract: Catalytic hydroamination reactions involving the addition of carboxamide, carbamates and sulfonamides to unactivated C=C bonds are briefly reviewed. Development in this field of catalytic research is briefly charted, followed by a discussion of possible mechanisms, including arguments to support the operation of both metal and Brønsted acid catalysis in these systems. Future developments in the area are summarised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 41 publications
1
40
0
5
Order By: Relevance
“…The result demonstrates the absence of any acidinduced transformation. There are reports warning of the possible action of acids as hydroamination catalysts [18,19] but they all concern less challenging processes such as intramolecular hydroaminations or the intermolecular addition across activated C=C bonds. Furthermore, the conditions employed here are not really acidic, as the amount of acid is a fraction of that of the amine (150 vs. 350 equiv.…”
Section: (C) Catalysis Of Transalkylation Processesmentioning
confidence: 99%
“…The result demonstrates the absence of any acidinduced transformation. There are reports warning of the possible action of acids as hydroamination catalysts [18,19] but they all concern less challenging processes such as intramolecular hydroaminations or the intermolecular addition across activated C=C bonds. Furthermore, the conditions employed here are not really acidic, as the amount of acid is a fraction of that of the amine (150 vs. 350 equiv.…”
Section: (C) Catalysis Of Transalkylation Processesmentioning
confidence: 99%
“…It was found that M 23 (B,C) 6 precipitates reduce the notch impact toughness in C–Mn–Mo steels when the boron content is 10–50 wt ppm. Boron may increase the susceptibility to temper embrittlement (TE) of steels in the tempering temperature range of 400–600 °C, more so in the absence of Mo . In oil‐quenched quench and tempered (QT) steels containing ≈0.003 wt% solute boron, boron was found to adversely affect the impact properties in larger cross sections, i.e., 26–51 mm bar diameter.…”
Section: Effect Of Boron On Toughness and Possible Mechanismsmentioning
confidence: 99%
“…[6] Compared to the catalytic processes related to intramolecular hydroaminations, the corresponding intermolecular reactions have been less studied since controlling the regioselectivity (Markovnikov vs. anti-Markovnikov selectivity) is challenging. [7] On the other hand, Gunnoe and coworkers described the anti-Markovnikov addition of aniline to styrene derivatives by using a well-defined copperamido catalyst [8] complexed with an N-heterocyclic carbene (NHC) ligand. The regioselectivity of Cu-catalyzed hydroaminations is known to be influenced by the catalytic system.…”
Section: Introductionmentioning
confidence: 99%